A Memory-Hard Function for Password Hashing and Key Derivation - Barros, Charles F. de (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2023)
Key derivation and password scrambling are crucial procedures in cryptographic applications, and the security of these methods against brute-force attacks is a critical concern in face of the increasing computational power available to perform these attacks. This paper proposes a candidate memory-hard function for password scrambling and key derivation, based on some design principles such as flexibility, variable-length output, adjustable parametrization to achieve high cache miss rates and dynamic update of the internal buffer.